A Moderation Analysis Of Digital Technology And Availment Of Financial Services Of Selected Personnel In State Universities And Colleges In The National Capital Region - Ria Santos Fajilago (Fakultas Bisnis - Institut Bio Scientia International Indonesia, 2025)
Financial inclusion is a critical driver of economic development, particularly among unbanked populations. In the Philippines, despite the widespread use of mobile phones, the adoption of mobile financial services remains low among low-income earners, especially among rank-and-file personnel such as janitors and security staff in State Universities and Colleges (SUCs) in the National Capital Region (NCR). This study investigates the relationship between the level of awareness of digital technology and the frequency of financial mobile service usage among these personnel. Using a quantitative descriptive research design, data were collected from 286 respondents across seven SUCs. The study measured awareness through indicators of digital technology knowledge, engagement, and decision-making, while financial service usage focused on payment transactions, money transfers, and remittances. Statistical analysis using Pearson correlation revealed a significant positive relationship between awareness of digital technology and financial service usage. The findings underscore the need for targeted digital literacy programs and policy reforms to enhance financial inclusion for underserved segments. This research contributes to the growing body of knowledge on the digital transformation of financial services and offers practical implications for educational institutions, financial service providers, and policymakers.